Comparative of Some Movement Abilities of Volley elite clubs Players According to their Specialties - Sabhan, Hussein; Saleh, Mohammed; Sattar, Kahlil (Journal of Physical Education, 2015)
For each sport activity, there is especial physical, kinetic, and mental abilities which differ from other activities and agree with the nature and rules of each game. Volleyball is one of these activities being unique in its physical, skillful or planned sides. As in almost all teams, each player has his own role in the game that helps in reaching high levels. Unique training is one of the basics in training as a whole. Hence, personal qualities should be taken into consideration in training volley players. Although coaches look for the uniqueness of each player in training, they do not have developed devices in measurements and diagnosis providing accurate data about the players' kinetic abilities. Actually, they depend on usual devices for measurement and diagnosis which are usually inaccurate and are somehow far from the recent scientific and technological devices which are followed in most modern countries. The development occurs in volleyball regarding its planning sides makes it urgent to look for specialty in performance. Each player has to be specialized in his own area due to his skillful, physical, kinetic, or mental abilities. The problem of the research concentrates on identifying the differences in kinetic abilities among players according to their places to help coaches make the training more unique and accurate especially in deciding the training curricula. The aim of the research is to identify the differences in the level of some kinetic abilities among volleyball players according to their places. The research hypothesizes that there are differences in the kinetic abilities among volleyball players provided with statistic designation. The descriptive style has been used being suitablefor this kind of researches. The corpora of the research are taken from the volleyball players of the professional league numbered (140) players. (56) players from (Gas Al-Ganoob, Al-Bahri, Al-Shurta, and Al-Sina'a) represent the data of the research which lasts from 2-2-2014 to 16-6-2014. The researchers have reached to the following: there are somehow differences in the level of kinetic abilities of the volleyball players. Thus, it is recommended that giving the coaches sufficient time in their exercises lessons is necessary in the process of training the kinetic abilities according to the specialty